PENERAPAN METODE SIMPLEKS UNTUK MEMAKSIMALKAN KEUNTUNGAN PENJUALAN PRODUK MENGGUNAKAN APLIKASI QM FOR WINDOWS(Studi Kasus : Kedai Kopi Dari Hati) - Intan Darwis; Jurniarti Sarmalina Duwiri, Mince Mentaneway, Rosia Karubaba, Brigita Griselda Thomas, Heru Sutejo (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2025)
This study aims to analyze the application of the simplex method in minimizing operational costs at the coffee business "Kopi Hati," located in Trisila, Polimak, Hamadi, and Koya. The approach used in this research is linear programming with the simplex method, applied to determine the optimal production combination of two main menu items: palm sugar coffee and cappuccino coffee. Fixed costs and variable costs per cup are used as the basis for the calculation model. The results show that the optimal solution is obtained at X1 (palm sugar coffee) = 4.2 cups per day and X2 (cappuccino coffee) = 3.2 cups per day, with a profit of IDR 275,000 per day from this production level. Thus, the simplex method proves to be helpful in identifying an efficient production strategy and in reducing total daily operational costs. Therefore, this method can serve as an effective decision-making tool for micro, small, and medium enterprises (MSMEs)